Air Service Boys Flying for Victory; Or, Bombing the Last German Stronghold - Beach, Charles Amory (Salt Lake City, UT : Project Gutenberg, 2008)
"Air Service Boys Flying for Victory; Or, Bombing the Last German Stronghold" by Charles Amory Beach is a novel likely written in the early 20th century, during or just after World War I. The book follows the adventures of two young American air pilots, Tom Raymond and Jack Parmly, as they engage in aerial battles and daring missions against German forces. The narrative is steeped in the intense atmosphere of the war, capturing the bravery and camaraderie of the protagonists as they face life-threatening challenges. The opening of the story sets the stage in the fall of 1918, as Tom and Jack await their signal to take off and join the fight over the Argonne Forest$1 (Ba crucial battleground. The boys are filled with excitement and tension as they discuss the dangers of aerial combat, and the reader is introduced to their personalities and motivations. As they ascend into the skies, the drama intensifies, showcasing Tom's close call with engine failure and their encounters with enemy planes. The camaraderie between the friends is palpable, and the stakes are raised as they navigate the dangers of their high-flying duties amidst the chaos of World War I. (This is an automatically generated summary.)s
Release date is 2008-07-07
E-text prepared by Juliet Sutherland, Emmy, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Aeronautics -- Juvenile fiction; World War, 1914-1918 -- Aerial operations -- Juvenile fiction; Parmly, Jack (Fictitious character) -- Juvenile fiction; Raymond, Tom (Fictitious character) -- Juvenile fiction; Air pilots, Military -- Juvenile fiction